Incorporating prediction and estimation risk in point-in-time credit portfolio models - Alfred Hamerle; Michael Knapp; Thilo Liebig; Nicole Wildenauer (Deutsche Bundesbank, 2005)
In this paper we focus on the analysis of the effect of prediction and estimation risk on the loss distribution, risk measures and economic capital. When variables for the determination of probability of default and loss distribution have to be predicted because they are not available at the time the prediction is made, the prediction is prone to errors. The model parameters for the estimation of probability of default or asset correlation are not available, and usually have to be estimated using historical data. The incorporation of prediction and estimation risk generally leads to broader loss distributions and therefore to rising values of risk parameters such as Value at Risk or Expected Shortfall. The level of economic capital required may be strongly underestimated if prediction and estimation risk are ignored.
Keywords: G21; C1; 330; probability of default; PD; credit risk; default correlation; asset correlation; point in time; value at risk; estimation risk; Kreditrisiko; Portfolio-Management; Schätzung; Statistischer Fehler; Prognoseverfahren; Value at Risk; Theorie; Deutschland